2017
DOI: 10.21511/bbs.12(4-1).2017.05
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Ukraine into the European banking system: cleaning, rebooting and Basel III

Abstract: The urgency of the issue is related to changes in the Ukrainian banks’ business environment, taking into account the impact of domestic and global financial instability and the implementation of the regulatory framework for banking regulation of the National Bank of Ukraine in accordance with the Basel Committee on Banking Supervision recommendations. The main goal of this research is to analyze the degree of implementation and compliance with the Basel III regulations in Ukrainian banking system. To carry out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Many domestic scholars, such as, in particular, E. Maslennikov et al (2017), A. Ramskyi et al (2017), O. Sobolieva-Tereshchenko (2018), S. Reverchuk et al (2015), O. Sobolieva-Tereshchenko and Y. Zhukova (2020), were engaged in researches of questions of essential organizational changes concerning Integration of Ukraine into the European banking system and institutional transformation. Thereby, it needs to study the market of payment cards in the analyzed countries on a number of criteria and identify trends in the use of payment cards for cashless payments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many domestic scholars, such as, in particular, E. Maslennikov et al (2017), A. Ramskyi et al (2017), O. Sobolieva-Tereshchenko (2018), S. Reverchuk et al (2015), O. Sobolieva-Tereshchenko and Y. Zhukova (2020), were engaged in researches of questions of essential organizational changes concerning Integration of Ukraine into the European banking system and institutional transformation. Thereby, it needs to study the market of payment cards in the analyzed countries on a number of criteria and identify trends in the use of payment cards for cashless payments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Maslennikov, Lomachynska, and Bychkova (2017) substantiated that increasing the number of banks with foreign capital has a positive effect on the adequacy of the regulatory capital of the banking system while increasing the number of banks with national capital has a negative effect. Ramskyi, Loiko, et al (2017) analyzed the main indicators of Ukrainian banks' financial stability from 2014 through 2017. As a result, they concluded that banks with foreign capital are the most stable in the Ukrainian banking system.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…We are going to consider the mentioned categories in the context of the Ukrainian financial market, and it is necessary to note some of its features. It is relatively young and is still at the stage of active development [8], it is floating to some extent, being in a state of uncertainty, in the process of transition from the post-Soviet model to European standards [9,10].…”
Section: Introductionmentioning
confidence: 99%